High-Volume Hospitals with High-Volume and Low-Volume Surgeons: Is There a "Field Effect" for Pancreaticoduodenectomy?. Issue 5 (May 2016) - Wood, Thomas W.; Ross, Sharona B.; Bowman, Ty A.; Smart, Amanda; Ryan, Carrie E.; Sadowitz, Benjamin; Downs, Darrell; Rosemurgy, Alexander S.
Since the Leapfrog Group established hospital volume criteria for pancreaticoduodenectomy (PD), the importance of surgeon volume versus hospital volume in obtaining superior outcomes has been debated. This study was undertaken to determine whether low-volume surgeons attain the same outcomes after PD as high-volume surgeons at high-volume hospitals. PDs undertaken from 2010 to 2012 were obtained from the Florida Agency for Health Care Administration. High-volume hospitals were identified. Surgeon volumes within were determined; postoperative length of stay (LOS), in-hospital mortality, discharge status, and hospital charges were examined relative to surgeon volume. Six high-volume hospitals were identified. Each hospital had at least one surgeon undertaking ≥ 12 PDs per year and at least one surgeon undertaking < 12 PDs per year. Within these six hospitals, there were 10 "high-volume" surgeons undertaking 714 PDs over the three-year period (average of 24 PDs per surgeon per year), and 33 "low-volume" surgeons undertaking 225 PDs over the three-year period (average of two PDs per surgeon per year). For all surgeons, the frequency with which surgeons undertook PD did not predict LOS, in-hospital mortality, discharge status, or hospital charges. At the six high-volume hospitals examined from 2010 to 2012, low-volume surgeons undertaking PD did not have different patient outcomes from their high-volume counterparts with respect to patient LOS, in-hospital mortality, patient discharge status, or hospital charges. Although the discussion of volume for complex operations has shifted toward surgeon volume, hospital volume must remain part of the discussion as there seems to be a hospital "field effect."